An Iodine‐Vapor‐Induced Cyclization in a Crystalline Molecular Flask. (6th April 2016) - Knichal, Jane V.; Shepherd, Helena J.; Wilson, Chick C.; Raithby, Paul R.; Gee, William J.; Burrows, Andrew D.
Abstract: A vapor‐induced cyclization has been observed in the host environment of a crystalline molecular flask (CMF), within which 1, 8‐bis(2‐phenylethynyl)naphthalene (bpen), a diarenynyl system primed for cyclization, was exposed to iodine vapor to yield the corresponding indeno[2, 1‐α]phenalene species. The cyclization process, unique in its vapor‐induced, solvent‐free nature, was followed spectroscopically, and found to occur concurrently with the displacement of lattice solvent for molecular iodine in CMF⋅0.75 bpen⋅2.25 CHCl3 ⋅H2 O. The cyclization occurred under mild conditions and without the need to suspend the crystals in solvent. The ability of CMFs to host purely gas‐induced reactions is further highlighted by the subsequent sequential oxidation reaction of cyclized 7‐iodo‐12‐phenylindeno[2, 1‐α]phenalene (ipp) with molecular oxygen derived from air, yielding 12‐hydroxy‐7‐iodo‐2‐phenylindeno[2, 1‐α]phenalen‐1(12 H )‐one (hipp). Abstract : Kristalliner Reaktionskolben : Die Ioddampf‐vermittelte Cyclisierung von bpen in das entsprechende Indeno[2, 1‐α]phenalen ipp in dem „kristallinen molekularen Reaktionskolben" [(ZnI2 )3 (tpt)2 ]⋅ x (G) (tpt=2, 4, 6‐Tris(4‐pyridyl)‐1, 3, 5‐triazin, G=Gast) wurde spektroskopisch untersucht. Die Cyclisierung verläuft unter milden Bedingungen und ohne Suspension der Kristalle in einem Lösungsmittel.